AB1305-HPR IS BETTER AND SAFER TOFACITINIB AS A FIRST LINE OF TREATMENT IN PATIENTS WITH RHEUMATOID ARTHRITIS? – A COHORT STUDY. (2nd June 2020) - Valencia, O.; Cabrera, M.; Rodriguez, F.; Santos-Moreno, P.
Abstract : Background: Tofacitinib is the first oral Janus Kinasa inhibitor approved for the treatment of rheumatoid arthritis (RA); and although it is approved both after conventional treatment and after biological therapy, it is not well known its real-life effectiveness in both cases and if it is preferable to use it after cDMARDs or biologics. Objectives: We compare the effectiveness and safety of Tofacitinib in patients with RA analyzing if better and safer Tofacitinib after cDMARDs or biologics. Methods: A retrospective analysis of a real-world cohort of patients with RA, who were treated with Tofacitinib in last 3 years, as first line of treatment (T1) after failure with cDMARDS and second line of treatment after biologic drug failure (T2). The therapy was considered effective with the change from moderate-high disease activity to low disease activity or remission measured by DAS28, in those who met criteria of high adherence, without change or addition of other conventional DMARDs, without new dose or increase of dose of oral glucocorticoids. A logistic model of regression was performed to evaluate de differences between T1 and T2, using as covariates sex, age, comorbidities, time of disease evolution, adverse events and other causes of discontinuation. Medication survival time and the main causes of suspension were measured. Mixed model regression and least-squared means were used to estimate the baseline changes and a Kaplan-Meyer survival analysis to estimate time to remission and drug survival. Results: 105 patients with RA were included (median age: 56.1 ± 11.7 years; 80.9% female, median disease duration 11.48 ± 10.1 years); 43% (45/105) of patients with positive rheumatoid factor and 73% (77/105) positive anti-citrulline antibodies. Regarding treatment 51% (54/105) used Tofacitinib as 1T, after failure to cDMARDs; on the other hand, Tofacitinib was used as 2T, after failure to biologics in 49% (51/105) of patients. DAS28 levels were reduced at 8, 16 and 24 weeks with statistical difference (p value 0.004, <0.0001, and <0.001, respectively). HAQ-DI also reported reduction but without statistical difference. The use of Tofacitinib was more effective after failure to cDMARDs (p value 0.014) and patients with more than 3 years of disease (p value 0.04), a statistically better response. Also, corticoids use, positive RF, extended release tablet of tofacitinib reported better changes of DAS28 but without statistical significance. Patients with high disease activity treated with Tofacitinib 1T decreased from 30% at baseline to 19% at the last follow-up; patients in 2T way were in moderate activity of the disease in 57% at baseline and went to 37% in the last follow-up. There was an increase in patients who achieved remission in both groups, but higher in 1T where they went from 9% to 41%, while in 2T they went from 22% to 33% (p < 0.05). The survival rate of the medication was 1.7 years in 1T and 2.1 in 2T; in terms of time to remission, the use of Tofacitinib monotherapy presented statistical difference (p value <0.001). The main cause of suspension of treatment was therapeutic failure 12% (13/105), 9% in 1T (5/54) and 16% (8/51) in 2T (p <0.005). 6% of patients (6/105) presented suspension due to the occurrence of adverse events, 4% (2/54) in 1T and 8% (4/51) in 2T (p <0.005). Conclusion: In patients with RA, the use of Tofacitinib as the first line of treatment (after failure to cDMARDs) is better in effectiveness and safer in comparison with its use as a second line of treatment (after biologics), with significant differences in the rates of therapeutic failure and occurrence of adverse events/reactions. On the other hand, concomitant corticoids use, positive RF, extended release tablet of Tofacitinib seem to increase the effectiveness of Tofacitinib in terms of DAS28 and HAQ-DI. Disclosure of Interests: Omaira Valencia: None declared, Michael Cabrera: None declared, Fernando Rodriguez: None declared, Pedro Santos-Moreno Grant/research support from: I have received research grants from Abbvie, Biopas-UCB, Janssen, Novartis, Pfizer., Speakers bureau: I have been a speaker for Abbvie, Biopas-UCB, Janssen, Lilly, Novartis, Pfizer, Roche, Sanofi.